Combined Effect of Compression Ratio and Fuel Injection Pressure on CI Engine Equipped with CRDi System Using Prosopis juliflora Methyl Ester/Diesel Blends. (29th April 2022) - Ramesh, T.; Sathiyagnanam, A. P.; De Poures, Melvin Victor; Murugan, P.
Abstract : The exhaustion of worldwide oil reserves has created an incipient need to find hopeful alternative fuels for the future. Substantial research has been done in this direction, and all studies by researchers have provided results that proved the growing potential of biofuel as a popular alternative in the CI engine. The current investigation explores the biofuel potential derived from the wasteland tree Prosopis juliflora (Karuvalam tree seeds). Experimentation was done using a monocylinder 4-stroke water-cooled six holes CRDi CI engine with electrical loading. The experiment was conducted at three proportions (10%, 20%, and 30% volume basis) of Prosopis juliflora Oil Methyl Ester (PJOME) with diesel using 3 parametric CRs (16, 17.5, and 19) along with three different fuel injection pressure (FIP) (400, 500, and 600 bar). The impact of CR and FIP on fuel utilization BTE, cylinder pressure, net heat release, and exhaust particulates was scrutinized and characterized. The test results demonstrated that increasing the compression ratio from 16 to 19 enhanced the in-cylinder pressure, net heat release (NHR), and BTE for all the (PJOME/Diesel) combinations. With an augmentation in the compression ratio from 16 to 19, carbon monoxide and unburnt hydrocarbon discharge diminished, but the nitrogen oxide discharges augmented. FIP also had an impact of increasing the pressures on the in-cylinder, NHR, brake thermal efficiency, and nitrogen oxide and reducing the emissions of smoke, CO, and UBHC. The current research shows that the use of B20 and CR16 and FIP 600 bar as a combination improved BTE by 33.21%, BSFC by 0.25 kg/kw-hr, cylinder pressure at the maximum to reach 69.28 bar, net heat release of 79.14 J/deg, and exhaust emissions such as UHC at 55 ppm, CO at 0.25%, smoke at 34.33%, and NOx at 2401 ppm. Finally, the BTE and NOx were slightly higher, and the UHC, CO, and smoke values were diminutive compared to other blends.